Mechanism of Cytosolic Phospholipase A2 Activation in Ghrelin Protection of Salivary Gland Acinar Cells against Ethanol Cytotoxicity - Bronislaw L. Slomiany; Amalia Slomiany (Advances in Pharmacological Sciences)
Ghrelin, a peptide hormone, newly identified in oral mucosal tissues, has emerged recently as an important mediator of the processes of mucosal defense. Here, we report on the mechanism of ghrelin protection against ethanol cytotoxicity in rat sublingual salivary gland cells. The protective effect of ghrelin was associated with the increase in NO and PGE2, and upregulation in cytosolic phospholipase A2 (cPLA2) activity and arachidonic acid (AA) release. The loss in countering effect of ghrelin occurred with cNOS inhibitor, L-NAME, as well as indomethacin and COX-1 inhibitor, SC-560, while COX-2 inhibitor, NS-398, and iNOS inhibitor, 1400W, had no effect. The effect of L-NAME was reflected in the inhibition of ghrelin-induced cell capacity for NO production, cPLA2 activation and PGE2 generation, whereas indomethacin caused only the inhibition in PGE2. Moreover, the ghrelin-induced up-regulation in AA release was reflected in the cPLA2 phosphorylation and S-nitrosylation. Inhibition in ghrelin-induced S-nitrosylation was attained with L-NAME, whereas the ERK inhibitor, PD98059, caused the blockage in cPLA2 protein phosphorylation as well as S-nitrosylation. Thus, ghrelin protection of salivary gland cells against ethanol involves cNOS-derived NO induction of cPLA2 activation through S-nitrosylation for the increase in AA release at the site of COX-1 action for PGE2 synthesis.